THE ROLE OF THE OUTSIDER IN CONTEMPORARY QUR’ANIC INTERPRETATION AND ITS INFLUENCE ON SHARI’A RULINGS - Azeez, Olalekan Rasheed; Olanrewaju, Yusuf Adam (Universitas Nurul Jadid, 2024)
Islam has been plagued by enemies who lie in wait, sparing no effort or expense to cast doubt upon it using various methods and techniques. The Islamic nation has faced significant threats from enemies since the Prophet's mission, including invasion of its thought, creed, heritage and history. Alienation in Exegesis (Tafsir) has caused confusion among Muslims, particularly in light of scientific discoveries, impacting rulings and the Qur'an's miraculous nature. This research examines the concept of infiltration and its effect on Islamic rulings. It explores the linguistic and terminological meaning of the word